Media Authenticity, Construction of Perpetrators' Motives, and Integration of Forensic Communication: The Investigation Process of Sexual Violence Cases in Online Media - Putra, Fajar Dwi; Unde, Andi Alimuddin; Cangara, Hafied; Sofyan, Andi Muhammad; Chang, Jian (Universitas Ahmad Dahlan, 2024)
This study explores the integration of forensic communication with media analysis to understand and address sexual violence. Media authenticity is examined as a crucial factor influencing public perception and judicial processes. Through a detailed examination of how media constructs motives and the application of forensic communication techniques, the research demonstrates the potential of mass media to serve as forensic evidence. The study employs an interpretive paradigm and Ricoeur's Hermeneutics of Suspicion to analyze media texts and police examination minutes. Findings indicate that the construction of motives in media significantly impacts the evidentiary process in sexual harassment cases. This research underscores the importance of accurate media representation and calls for the media to adhere to accuracy, integrity, and social responsibility principles. Further research is suggested to explore the broader social dynamics and collective motives in criminal cases, particularly sexual violence.